Molecular Guided Therapy Provides Sustained Clinical Response in Refractory Choroid Plexus Carcinoma - Cornelius, Albert; Foley, Jessica; Bond, Jeffrey; Nagulapally, Abhinav B.; Steinbrecher, Julie; Hendricks, William P. D.; Rich, Maria; Yendrembam, Sangeeta; Bergendahl, Genevieve; Trent, Jeffrey M.; Sholler, Giselle S. (Frontiers in Pharmacology, 2017)
Choroid plexus carcinomas (CPCs) are rare, aggressive pediatric brain tumors with no established curative therapy for relapsed treatment, and poor survival rates. TP53 Mutation or dysfunction correlates with poor or no survival outcome in CPCs. Here, we report the case of a 4 month-old female who presented with disseminated CPC. After initial response to tumor resection and adjuvant-chemotherapy, the tumor recurred and metastasized with no response to aggressive relapse therapy suggesting genetic predisposition. This patient was then enrolled to a Molecular Guided Therapy Clinical Trial. Genomic profiling of patient tumor and normal sample identified a TP53 germline mutation with loss of heterozygosity, somatic mutations including IDH2, and aberrant activation of biological pathways. The mutations were not targetable for therapy. However, targeting the altered biological pathways (mTOR, PDGFRB, FGF2, HDAC) guided identification of possibly beneficial treatment with a combination of sirolimus, thalidomide, sunitinib, and vorinostat. This therapy led to 92% reduction in tumor size with no serious adverse events, excellent quality of life and long term survival.